Prominence activation, optical flare, and post-flare loops on the RS Canum Venaticorum star SZ Piscium. Issue 1 (13th October 2018) - Cao, Dongtao; Gu, Shenghong; Ge, Jian; Wang, Tinggui; Zhou, Jilin; Chang, Liang; Wolter, U; Mittag, M; Schmitt, J H M M; Perdelwitz, V
Abstract: We present the results of time-resolved high-resolution spectroscopic observations of the very active RS Canum Venaticorum (RS CVn) star SZ Piscium (SZ Psc), obtained during two consecutive observing nights on 2011 October 24 and 25. Several optical chromospheric activity indicators are analysed using the spectral subtraction technique, which show the remarkably different behaviour between two nights. Gradually blue-shifted and strengthened excess absorption features presented in the series of the subtracted spectra (especially for the Hα, He I D3, and Hβ lines), as a result of active stellar prominence that is rising its height along the line of our sight, was detected in the observations on October 24. This prominence activation event was probably associated with the subsequently occurred optical flare, and part of that flare decay phase was hunted in the observations on October 25. The flare was characterized by the prominentHe I D3 line emission, as well as stronger chromospheric emission in the Hα, Hβ, and other active lines. The gradual decay of flare was accompanied by an obviously developmental absorption feature in the blue wing of the Hα and other active lines, which could be explained as cool post-flare loops which projected against the bright flare background. Therefore, a series of possibly associated magnetic activity phenomena, including flare-related prominence activation, optical flare, and post-flare loops, were detected during our observations.